Principles of Protein Structure - G E Schulz (Springer (India) Pvt. Ltd, 2009)
New textbooks at all levels of chemistry appear with great regularity. Our goal, in this series, is to pinpoint areas of chemistry where recent progress has outpaced what is covered in any available textbooks, and then seek out and persuade experts in these fields to produce relatively concise but instructive introductions to their fields